Undergraduate and graduate philosophy theses defended at the University of Costa Rica (1944–2024): Analysis of a Topic in the History of Costa Rican Philosophical Thought - Herrera Luna, Ricardo J. (2025)
This paper aims to examine the dissertations presented in the field of philosophy at the University of Costa Rica during the years comprehended between1944 and 2024 in order to contribute with evidence that will broaden the proposal in the book Crítica de los guardianes del reino (Arlekín, 2018) wich argues that the seventies, in the twentieth century, had a significant impact as a new way to produce philosophy in Costa Rica.